Modern and renewable materials in civil engineering - Brozovsky, Jiri (Key engineering materials, 2020)
Prepared to the 20th Anniversary of the Faculty of Civil Engineering of the VSB - Technical University of Ostrava Special topic volume with invited peer reviewed papers only.